The Therapeutic Role of Olea europaea in Alcohol Dependence Base in Network Pharmacology Analysis - Awwaluddin, Faiznanda; Jamil, Ahmad Shobrun; Rofida, Siti; Muchlisin, M Artabah (Proceedings of International Pharmacy Ulul Albab Conference and Seminar (PLANAR); Vol 3 (2023): Proceedings of International Pharmacy Ulul Albab Conference and Seminar (PLANAR), 2023)
Alcohol dependence is a state of alcohol becoming a vital part of the life of a person who consumes it; when discontinued, it can lead to a wide range of physical and mental health disorders as well as a decrease in life productivity in people with alcohol dependence. Olea Europaea (OE) is a plant capable of treating alcohol dependence. The method used in silico-based pharmacological grid analysis to determine the ability of the OE compound to treat alcohol dependence. EO compound data is obtained from the KnapSack database, absorption, distribution, metabolism, and excretion (ADME) screening using SwissADME, target protein prediction using SwissTargetPrediction, Gene cards, venny, pharmacological grid analysis with String-DB, visualization with Cytoscape 3.10.0. Results are obtained from 63 OE compounds, and 17 have ADME criteria matching the drug compounder (Drug Likeness/DL). The pathways that correlate with therapy are dopamine receptors, dopamine transporter, serotonin receptor, gamma-aminobutyric acid receptor, and toll-like receptors for known therapeutic target proteins: OPRM1, DRD2, ALDH2, ADH1B, ADH1A, ADH1C, ADH4, ADH7, SLC6A3, CNR1, POMC, ARRB2, and NCS1. Compounds associated with alcohol dependency therapy include Hexanal, Nonadienal, Octanal, 3-Hexenal, 3-Methyl-butanal, Methyl nominate, Cinchonidine, cinchonine, (9S)-10,11-Dihydrocinchonan-9-ol, Oleuropeic acid, Butyl acetate, cis-3-hexenyl acetate, and (S)-2,3-Epoxysqualene. Based on the findings, OE is a potential drug candidate for alcohol dependence.